Effects of the type and proportion of a binder on the quality and combustion of fuel pellets; Biomass and Bioenergy; Vol. 199 - Nyashina G. S. Galina Sergeevna; Dorokhov V. V. Vadim Valerjevich; (Shvedov D. K. Denis Konstantinovich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen